Innovation and Collaboration Model Based on Ecological Fiscal Transfer Approach: Case Study on Green Siak Regency Policy Development - Wicaksono Baskoro; Marta Auradian; Febrina Rury; Rafi Muhammad; Gusmansyah Gusmansyah; Hergianasari Putri (E3S Web of Conferences)
In 2018, the Siak Regency Government initiated the Siak Green policy innovation based on Siak Regent Regulation Number 22 of 2018 concerning Siak Green Regency, which aims to overcome the impact of environmental damage and the implementation of sustainable development goals, where the regulation is used as a guideline for all parties in collaborating to implement sustainable natural resource management for the welfare of the Siak community. This study aims to analyse existing conditions and design an innovation and collaboration model based on an ecological fiscal transfer approach in developing the Siak Green Regency policy. This study uses a qualitative descriptive approach, where primary and secondary data sources related to the Siak Green Regency policy are analysed using NVivo12 Plus software to be able to answer research questions systematically. Based on the results of the analysis, this study found that the existing conditions of the Siak Green policy are still sectoral and have yet to be integrated into the work plans of regional apparatuses and related stakeholders. Substantively, the ecological fiscal transfer approach is an innovative and crucial policy instrument that needs to be adopted to maintain the sustainability of forest areas in Siak Regency while continuing to encourage increased stakeholder collaboration through fiscal transfers and intergovernmental revenue sharing schemes based on ecological indicators as awards given based on the quality-of-life index in sustainable conservation efforts in Siak Regency.